Establishment of typical adult CT dose indicators for PET-CT scans in Slovenia. (19th August 2021) - Perić, Jelena; Mekiš, Nejc; Žontar, Dejan
Abstract: The aim was to determine typical values of diagnostic reference level (DRL) quantities for the computed tomography (CT) part of the most common positron emission tomography—computed tomography (PET-CT) procedures in Slovenia. The most common PET-CT procedures were identified, and data collated for 565 patients imaged in all three PET-CT units in Slovenia during a time span of 11 months. As the number of facilities is too low to establish national DRLs, we followed ICRP recommendations and determined typical values of DRL quantities as the median values of the pooled set of data. Mean, median, and standard deviation of CT dose index (CTDIvol ) and total dose length product (DLP) for the CT part of the most common PET-CT procedures were determined for pooled data as well as for each PET-CT unit. The data were compared between all three units to identify possible outliers that would likely benefit from optimization. Three most common CT protocols covering approximately 2/3 of all PET-CT imaging performed in Slovenia were considered: from the base of the cranium to the middle of the femur, from the top of the head to the middle of the femur, and for the whole-body PET-CT. The established typical values in terms of total DLP were 295, 359, and 676 mGy⋅cm, respectively; and in terms of CTDIvol 3.05, 3.22, and 3.60 mGy, respectively. Comparing the data between all three units showed significantly higher ( p < 0.001) patient doses on one unit, indicating a need for optimization. The results present the first-time data on the national typical values of DRL quantities for the CT part of most common PET-CT procedures in Slovenia. While the determined typical values are within the DRL values established in some other countries, significant differences were found between the individual units included in the study.